2021
DOI: 10.3389/fmicb.2021.662907
|View full text |Cite
|
Sign up to set email alerts
|

Connection Between Chromosomal Location and Function of CtrA Phosphorelay Genes in Alphaproteobacteria

Abstract: Most bacterial chromosomes are circular, with replication starting at one origin (ori) and proceeding on both replichores toward the terminus (ter). Several studies have shown that the location of genes relative to ori and ter can have profound effects on regulatory networks and physiological processes. The CtrA phosphorelay is a gene regulatory system conserved in most alphaproteobacteria. It was first discovered in Caulobacter crescentus where it controls replication and division into a stalked and a motile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The strongest conservation of GTA gene cluster localization is also found in this order, where it is biased towards ter. This is in accordance with our previous study where the Rhodobacterales ctrA gene was also found conserved near to ter and showed the lowest number of GANTC motifs in ctrA promoter regions [56]. Hemi-methylation of this motif during replication has been found to be a signal for transcriptional activation [57].…”
Section: Between Potential Dna Methylation Sites Gta Gene Cluster Loc...supporting
confidence: 92%
“…The strongest conservation of GTA gene cluster localization is also found in this order, where it is biased towards ter. This is in accordance with our previous study where the Rhodobacterales ctrA gene was also found conserved near to ter and showed the lowest number of GANTC motifs in ctrA promoter regions [56]. Hemi-methylation of this motif during replication has been found to be a signal for transcriptional activation [57].…”
Section: Between Potential Dna Methylation Sites Gta Gene Cluster Loc...supporting
confidence: 92%
“…A current study across 773 species, covering all major bacterial taxa, found conserved positions on the chromosome, in particular a bias towards ori and ter , for almost half of the identified gene families [33]. The ori - or ter -proximal position of regulatory genes can be strongly conserved across an order but can also show distinct evolutionary trajectories between phyla [34,35]. Exceptional genome architectures, defying the general evolutionary trend within a phylum, have also been found [30,36].…”
Section: Discussionmentioning
confidence: 99%
“…A current study across 773 species, covering all major bacterial taxa, found conserved positions on the chromosome, in particular a bias toward ori and ter , for almost half of the identified gene families ( 34 ). The ori - or ter -proximal position of regulatory genes can be strongly conserved across an order but can also show distinct evolutionary trajectories between phyla ( 35 , 36 ). Exceptional genome architectures, defying the general evolutionary trend within a phylum, have also been found.…”
Section: Discussionmentioning
confidence: 99%